The Relationship of Organizational Commitment with Organizational Citizenship - Alifia, Salsabila Sarsa; Ulya, Laila Listiana (Journal of Social and Industrial Psychology, 2023)
Employees with high OCB levels are able to increase productivity and provide a good future for the company. OCB can be influenced by internal factors and external factors. One of the internal factors that influence OCB is organizational commitment. This study aims to determine the relationship between organizational commitment and Organizational Citizenship Behavior. Using a correlational quantitative approach, this study involved 141 production employees at PT. X Semarang was selected through a, purposive sampling technique. The research data was taken using the organizational commitment scale and the OCB scale. Furthermore, the data were analyzed using the Kendall or non-parametric correlation technique. The result of the correlation coefficient between organizational commitment and OCB variables is 0.153 with a significance level of p=0.005 where p<0.05. These results indicate that there is a positive relationship between organizational commitment and OCB. So it can be concluded that the production employees of PT. X Semarang has a good commitment so that employees are able to show good OCB to fellow employees and to the company